Pious fashion how Muslim women dress - Bucar, Elizabeth M. (Harvard University Press, 2017)
For many westerners, the veil is the ultimate sign of women's oppression. But Elizabeth Bucar's take on Muslim women's clothing is a far cry from this attitude. She invites readers to join her in three Muslim-majority nations as she surveys pious fashion from head to toe and shows how Muslim women approach the question "What to wear?" with style.